Comparison of Efficacy of Ultrasound Guided Erector Spinae Block vs Paravertebral Block for Postoperative Analgesia in Breast Surgeries - B Arun Kumar; T Divyalakshmi; R Brindha; Naveena Pandian; Panneerselvam Periasamy (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Effective management of postoperative pain (PSP) following breast surgeries is essential to improving recovery and preventing chronic pain syndromes. While the thoracic paravertebral block (TPVB) is the established standard for analgesia in breast surgeries, the erector spinae plane block (ESPB) has recently emerged as a simpler and safer alternative. Aim: To compare the efficacy of ultrasound-guided erector spinae block (ESPB) versus paravertebral block (TPVB) for postoperative analgesia in breast surgeries. Methods: A prospective randomized study was conducted on 60 patients undergoing elective breast surgeries at Vinayaka Missions Kirupananda Variyar Medical College and Hospitals, Salem. Patients were randomized into two groups: Group A (ESPB, 0.125% ropivacaine + dexmedetomidine) and Group B (TPVB, 0.125% ropivacaine + dexmedetomidine). Pain was assessed using the Visual Analog Scale (VAS) over 24 hours post-surgery. Secondary outcomes included hemodynamic stability, duration of sensory blockade, rescue analgesic requirements, and complications. Data were analyzed using EPI 2010 software. Results: Baseline hemodynamic parameters were comparable between the groups, except for higher systolic blood pressure (142.1 ± 3.8 mmHg vs. 136.5 ± 7.8 mmHg, P < 0.001) and VAS scores (4.5 ± 0.9 vs. 3.5 ± 0.8, P < 0.001) in Group B. Postoperatively, VAS scores were significantly lower in Group A from the 4-hour mark onwards (P < 0.006), indicating superior analgesic efficacy. Hemodynamic parameters, including heart rate and diastolic blood pressure, remained stable and comparable between the groups. No significant complications were observed in either group. Conclusion: Ultrasound-guided ESPB provides superior postoperative analgesia compared to TPVB, with consistent pain relief and similar hemodynamic stability. Its simplicity and safety profile make ESPB a promising alternative for pain management in breast surgeries. Further studies are warranted to validate these findings and optimize analgesic protocols.